Pengaruh Gaya Kepemimpinan Dan Disiplin Kerja Terhadap Kinerja Karyawan Pabrik The PT. Sumatera Toba Wangi - Ayu Wahyudin; Kusuma Agdhi Rahwana; Gian Riksa Wibawa (UNIVERSITAS MARITIM AMNI SEMARANG, 2023)
This study aims to determine the simultaneous and partial effect of Leadership Style and Work Discipline on Employee Performance at the Tea Factory of PT. Sumatra Toba Wangi. The research method used in this study is to use a quantitative research method with a questionnaire. The population in this study were employees of the Tea Factory of PT. Sumatra Toba Wangi as many as 50 employees. The type of data used in this study is primary data obtained through questionnaires. The data testing technique used in this study uses the validity test, reliability test and classic assumption test. Data analysis in this study used multiple regression analysis using SPSS software version 25. The results showed that Leadership Style and Work Discipline simultaneously had a significant effect on Employee Performance at the Tea Factory of PT. Sumatra Toba Wangi. Leadership Style partially has a significant effect on Employee Performance at the Tea Factory of PT. Sumatra Toba Wangi. Work Discipline partially has a significant effect on Employee Performance at the Tea Factory of PT. Sumatra Toba Wangi.